Kitchens, now and long ago - Purkis, Sallie (London : Longman, 1998)
This book tells how kitchens have changed over one hundred years. It also tells what kitchens were like fifty years ago and what they are like nowadays.
Keywords: Houses -- history; Kitchens -- history